2004
DOI: 10.1254/jphs.fp0040359
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of FR194921, a New Potent, Selective, and Orally Active Antagonist for Central Adenosine A1 Receptors

Abstract: Abstract. Adenosine A 1 receptors in the brain are believed to play an important role in brain functioning. We have discovered a novel adenosine A 1 receptor antagonist, FR194921 (2-(1-methyl-4-piperidinyl)-6-(2-phenylpyrazolo[1,5-a]pyridin-3-yl)-3(2H)-pyridazinone), and characterized the pharmacological activity in the present study. FR194921 showed potent and selective affinity for the adenosine A 1 receptor without affinity for A 2A and A 3 receptors and did not show any species differences in binding affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 37 publications
(34 reference statements)
1
61
0
1
Order By: Relevance
“…Currently, there is a great deal of interest in developing new drugs with minimal adverse effects to treat anxiety disorders (13,14). Among the candidate approaches, many studies have also suggested that the N/ OFQ peptide and the NOP-receptor system are promising targets (15).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a great deal of interest in developing new drugs with minimal adverse effects to treat anxiety disorders (13,14). Among the candidate approaches, many studies have also suggested that the N/ OFQ peptide and the NOP-receptor system are promising targets (15).…”
Section: Discussionmentioning
confidence: 99%
“…FR194921 was orally active and centrally available, ameliorated scopolamineinduced memory deficits, and also showed anxiolytic effects in the elevated plus maze test, without influencing general behaviour or having antidepressant activity 107 .…”
Section: Dementia and Anxiety Disordersmentioning
confidence: 99%
“…Recently, the novel A 1 AR-selective antagonist FR194921 (which did not show any species differences in its high A 1 AR affinity) was reported to have potential in the treatment of dementia and anxiety disorders 107 . FR194921 was orally active and centrally available, ameliorated scopolamineinduced memory deficits, and also showed anxiolytic effects in the elevated plus maze test, without influencing general behaviour or having antidepressant activity 107 .…”
Section: Dementia and Anxiety Disordersmentioning
confidence: 99%
“…Die kognitiewe effekte van kafeïen kan merendeels toegeskryf word aan sy vermoë om adenosien A 1 -reseptore in die hippokampus en prefrontale korteks van die brein te antagoniseer (Ribeiro & Sebastião 2010). Hierdie breinareas word normaalweg met kognitiewe funksies geassosieer (Maemoto et al 2004). Adenosien A 1 -antagoniste depolariseer neurone wat postsinapties voorkom en verhoog die presinaptiese vrystelling van 'n aantal neurotransmitters soos asetielcholien, glutamaat, serotonien en norepinefrien.…”
Section: Inleidingunclassified